Correlation Parenting Styles on Children's Health Behaviors during Pandemic Covid-19 at MI Nurul Huda Wadeng Gresik - Chilyah Faiqotun Nuriyah selly; Lantin Sulistyorini; Peni Perdani Juliningrum (KHD-Production, 2021)
School-age children who are growing up are vulnerable to the risk of COVID-19 disease transmission, therefore it is required to apply healthy living behaviors in the application of new habit adaptation, such as washing hands using water and soap, wearing masks, keeping a distance, doing sports, and eating nutritious diet. Parenting is expected to keep children’s healthy by giving the right habits. Children would obey in healthy behavior. The aims to determine the correlation between parenting and health behavior during the pandemic of school children at MI Nurul Huda Wadeng, Gresik. Cross-sectional approach correlational research design. Sampling using simple random sampling with 127 samples which are parents of children. Data collection used a parenting style questionnaire and a Likert scale for healthy behavior during the pandemic in google form. Data analysis used the Kendall-tau test. The results showed that there was a relationship between parenting and health behavior during the pandemic (p-value = 0.009; τ = 0.218). Parent who use authoritative parenting would make children have good behavior, and if parent use authoritarian parenting, child's health behavior will be lower. Applying authoritative parenting will be easier to take an optimal approach. Keywords: Parenting Styles, Children's Health Behaviors during Pandemi, Authoritative, Authoritarian, Permissive.